Firearm homicides in Europe: a comparison with non-firearm homicides in five European countries - Krüsselmann, Katharina (Global crime, 2023)
Detailed, comparative research on firearm violence in Europe is rare. Using data from the European Homicide Monitor, this paper presents the prevalence and characteristics of firearm homicides in Denmark, Finland, the Netherlands, Sweden and Switzerland between 2001 and 2016. Furthermore, we compare firearm to non-firearm homicides to assess the degree of uniqueness of firearms as modus operandi. We find that the firearm homicide rate varies across our sample of countries. We also identify two country profiles: in Denmark, the Netherlands and Sweden, most firearm homicides take place in public and urban areas, involving male victims and perpetrators. In these countries, the use of firearms in homicides is largely concentrated in the criminal milieu. In Finland and Switzerland, firearms are mostly used in domestic homicides, with a higher share of female victims. We explore these findings in relation to firearm availability in each country.